Capable Infection of Hepatitis B Virus in Diffuse Large B-cell Lymphoma - Wang, Yanchun (J Cancer, 2018)
Background: Diffuse large B-cell lymphoma (DLBCL) is the most common pathological type of non-Hodgkin lymphoma (NHL). It is strongly correlated to the host immunity and infection status. Aim: This study tested the hypothesis that hepatitis B virus (HBV) infection is also associated with DLBCL. Methods: Clinical analysis of the correlation between DLBCL and HBV infection, detection of HBV in situ of DLBCL tissue, and biological experiments that determined whether HBV infects B lymphocytes were conducted. Results: Our long-term clinical data showed that the positive rate of serum HBV was significantly increased in DLBCL patients (23.6%) compared to that in the general Chinese population (7.2%, P<0.001), especially in advanced stage lymphoma patients (P=0.003). In addition, HBV could infect B lymphocytes in vitro and the HBV antigen and nucleic acid could be detected intracellularly. Hepatitis B x protein (HBx) was also strongly expressed in tissues from DLBCL patients that were serum HBV surface antigen (HBsAg) positive. These patients responded less well to therapy with an odds ratio (OR) of 3.04. Conclusions: HBV can infect B lymphocytes. It might be related to the development of DLBCL and may also impact the efficacy of treatment.